8‐Aminoquinolines with an Aminoxyalkyl Side Chain Exert in vitro Dual‐Stage Antiplasmodial Activity. (14th January 2019) - Leven, Michael; Held, Jana; Duffy, Sandra; Alves Avelar, Leandro A.; Meister, Stephan; Delves, Michael; Plouffe, David; Kuna, Krystina; Tschan, Serena; Avery, Vicky M.; Winzeler, Elizabeth A.; Mordmüller, Benjamin; et al.
Abstract: A series of novel 8‐aminoquinolines (8‐AQs) with an aminoxyalkyl side chain were synthesized and evaluated for in vitro antiplasmodial properties against asexual blood stages, liver stages, and sexual stages of Plasmodium falciparum . 8‐AQs bearing 2‐alkoxy and 5‐phenoxy substituents on the quinoline ring system were found to be the most promising compounds under study, exhibiting potent blood schizontocidal and moderate tissue schizontocidal in vitro activity. Abstract : Among the approved antimalarials, 8‐aminoquinolines (8‐AQs) are especially important because they are able to prevent P. vivax relapse. To obtain further insight into the structure–activity relationships of 8‐AQs, we replaced the terminal amino group of reference compounds primaquine and tafenoquine with an aminoxy group. Some of the new oxa‐analogues bearing 2‐alkoxy and 5‐phenoxy substituents exhibited IC50 values in the range of the two reference compounds.